Accessibility of Patients With Special Healthcare Needs to Dental Care in the Eastern Province of Saudi Arabia: A Multicentre Study From Perspective of Caregiver and Dental Care Providers - Tarek Ezzeldin; Mazin Algahtani; Nadia Abdulrahman Alghannam; Faisal Abdulkareem Alsafran; Intisar Ahmad Siddiqui; Hebah Zaki Al-Ghanim; Basma Mohamed Bader; Abdullah Abdulatif Alshubat; Adnan Hamad Almarry; Hussein Hejji IbnAhmed; Sarah Abdulhadi Kanakri; Reem Babiker Eltayeb; et al. (The Scientific World Journal)
Dental care accessibility is subject to a dentist’s qualification, practice and intention to treat patients, regardless of whether those patients have special healthcare needs (SCN) and should receive treatment in a dental setting. This multicentre study aimed to evaluate the characteristics of patients with SCN, their access to dental care and behaviour towards dental care from their caregiver’s perspective. In addition, the perspective of dental care providers who care for patients with SCN and the factors affecting the provision of treatment was also appraised. The Eastern Province of Saudi Arabia served as the site of this cross-sectional study from 1 February 2020 to 31 January 2022. Caregivers of 272 patients with SCN, regardless of age and gender, were recruited in the study. The caregiver’s proforma sought information on the demographic characteristics, type of disability, cooperation, medical history, occupation of the parent and patient’s behaviour towards oral hygiene and dental healthcare. The second proforma had the dental care provider’s perspective about the common disabilities, factors that affect the decision to provide treatment, difficulties patients face in getting their dental treatment and, from the dentist’s experience, recommendations to improve the access to dental care for patients with SCN. Statistical analysis was carried out by using SPSS version 22.0. The demographic features, caregiver’s perception about oral healthcare accessibility and dental professional’s point of view were presented as frequencies and percentages. Chi-square test was applied to compare the proportions. The majority of the caregivers were satisfied with the dental service providers (91.9%) for their patients with SCN. The dental care provider’s survey results indicated a shortage of dentists (54.7%) in the region and other factors that pose challenges to special care, like the severity of the disability of patients with SCN (50%), family structure (46.7%), treatment cost (35.6%) and transportation (32.8%). Patients with SCN in Saudi Arabia had a high appraisal of access to dental care and were very satisfied with dental treatment results. However, the presence of a dental care provider in the same rehabilitation centre was a major concern. The severity of the disability and the patient’s cooperation were the major factors that may have affected the decision of the dental care provider.